2019
DOI: 10.1186/s13063-019-3319-2
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde Inferior Vena caval Perfusion for Total Aortic arch Replacement Surgery (RIVP-TARS): study protocol for a multicenter, randomized controlled trial

Abstract: Background During total aortic arch replacement surgery (TARS) for patients with acute type A aortic dissection, the organs in the lower body, such as the viscera and spinal cord, are at risk of ischemia even when antegrade cerebral perfusion (ACP) is performed. Combining ACP with retrograde inferior vena caval perfusion (RIVP) during TARS may improve outcomes by providing the lower body with oxygenated blood. Methods This study is designed as a multicenter, computer-ge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The combination of ACP and RIVP, in contrast, shows promise as a safe and effective technique during circulatory arrest, which we are investigating in a multicenter randomized controlled trial. 5…”
Section: Resultsmentioning
confidence: 99%
“…The combination of ACP and RIVP, in contrast, shows promise as a safe and effective technique during circulatory arrest, which we are investigating in a multicenter randomized controlled trial. 5…”
Section: Resultsmentioning
confidence: 99%
“…This has reduced rates of mortality and neurological complications, yet rates of organ dysfunction in the lower body remain high as a result of inadequate perfusion. For example, rates of spinal ischemia or hemiplegic paraplegia range from 4% to 25%, while rates of dialysis range from 6% to 18% ( 17 ). These adverse events likely become more frequent with longer circulatory arrest.…”
Section: Discussionmentioning
confidence: 99%
“…The second is the combination of DHCA with antegrade cerebral perfusion (ACP) or retrograde cerebral perfusion (RCP), which may provide blood flow to the brain, but which still leaves the lower body at risk of ischemia. The third is the combination of DHCA with total body perfusion, which can be achieved through the arterial or venous systems, or through our recently proposed combination of ACP with retrograde inferior vena caval perfusion (RIVP) ( 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…After the widespread use of anterograde or retrograde cerebral perfusion to protect the brain during aortic arch replacement surgery, researchers have focused on how to minimize ischemic injury to the lower body during the operation. We reported that anterograde cerebral perfusion combined with retrograde inferior vena caval perfusion provides continuous blood ow to the brain, abdominal viscera, and spinal cord during HCA [2][3][4] . However, this technique requires cross-clamping three arterial branches of the aortic arch, which is unnecessary during HRS.…”
Section: Discussionmentioning
confidence: 99%